2000
DOI: 10.1093/humrep/15.11.2360
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-individual variability in human sperm concentration, motility and vitality assessment during a workshop involving ten laboratories

Abstract: The aim of the present study was to assess variability in the evaluation of human sperm concentration, motility and vitality. Technicians and biologists from 10 teams involved in multicentre studies on semen quality attended the same laboratory, each team using its own methods and equipment to analyse the same semen samples. Inter-individual variability was assessed from 17 fresh semen samples of varying quality. Intra-individual variability was assessed from pools of frozen samples for sperm concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
100
1
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 21 publications
11
100
1
6
Order By: Relevance
“…Furthermore, the mean number of spermatozoa analyzed in our series was 126±36 for the ICSI selected sample and 82±41 for MSOME; both numbers were much higher than that previously reported (9±7) [10]. Even though the effect on spermatogenesis varies from one type of translocation to another [29], there are also significant inter-individual variations for a given translocation [2,14,22]. In infertile populations with implantation failure, the use of IMSI reportedly increases the pregnancy rate.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, the mean number of spermatozoa analyzed in our series was 126±36 for the ICSI selected sample and 82±41 for MSOME; both numbers were much higher than that previously reported (9±7) [10]. Even though the effect on spermatogenesis varies from one type of translocation to another [29], there are also significant inter-individual variations for a given translocation [2,14,22]. In infertile populations with implantation failure, the use of IMSI reportedly increases the pregnancy rate.…”
Section: Discussioncontrasting
confidence: 56%
“…They suggested that different count chambers, different dilutions applied for high concentrations and the use of different pipettes could be the reason for this large variation. However, as the highest quantity we analysed was 84.5 millions/ml in comparison with the 20% of samples that had a higher concentration in Auger et al (7), it is reasonable to consider that the dilution factors had less influence in our coefficients of variation.…”
Section: Discussionmentioning
confidence: 61%
“…In a more recent study, Auger et al (7) reported that the variations found in semen analysis are higher when high concentration levels are analysed. They suggested that different count chambers, different dilutions applied for high concentrations and the use of different pipettes could be the reason for this large variation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most laboratories manually assess semen under a microscope. However, conventional manual semen analysis has limitations, as illustrated by studies demonstrating inter-lab variability engendering discordant results that can cause inappropriate diagnosis or delayed treatment of infertile couples [3]. Keel et al (2000) analyzed the results of the American Association of Bioanalysts national proficiency testing programme in andrology [4].…”
Section: Introductionmentioning
confidence: 99%